Season but not sex influences burrow length and complexity in the non-sexually dimorphic solitary Cape mole-rat (Rodentia: Bathyergidae) - Thomas, H.; Bateman, Bill; Scantlebury, M.; Bennett, N. (Wiley-Blackwell Publishing Ltd., 2012)
Little is known about how season influences burrowing activity, burrow structureor reproductive behaviour in subterranean mammals. We excavated burrowsystems of male and female Georychus capensis, a solitary, subterranean rodent, inwinter (wet season) and summer (dry season) to investigate whether, if any,seasonal differences were due to putative mate-seeking behaviour of males.Burrow structure differed between seasons but not between sexes. For both sexes,summer burrows were shorter and covered a smaller area, but explored the surroundingenvironment more efficiently than winter burrows. Summer burrowshad fewer mounds, which indicated that less expansion of the burrow systemsoccurred during this season. We discuss these differences in exploration and theuse of the environment between seasons in terms of mating strategies of G. capensisand observed levels of sexual dimorphism in our populations. This studysupports recent ideas regarding sexual selection relating to exaggerated traits infemales, which affect a female’s ability to acquire reproductive resources that oftenappear similar to that selected for by males.